Early and Regular Bronchoscopy Examination on Effect of Diagnosis and Prognosis for Patients With Tracheobronchial Tuberculosis - Hu, Tingting; Li, Yishi; Wang, Xiaohui; Chen, Yan; Nie, Xiao; Zhuang, Rongjuan; Li, Ying; Guo, Shuliang (Frontiers in Medicine, 2022)
Background Bronchoscopy is the main method for the diagnosis of tracheobronchial tuberculosis (TBTB). However, it is not well-used in patients with pulmonary tuberculosis (PTB), leading to misdiagnosis. The aim of this study is to verify the value and feasibility of bronchoscopy for an early diagnosis and treatment of TBTB. Materials and Methods A prospective observational study was performed in patients with active PTB. The ratios of TBTB and tracheobronchial stenosis were analyzed with propensity score matching (PSM) for baseline characteristics, and a Cox regression model was further employed to adjust for residual confounding factors. Results A total of 656 patients with active PTB were enrolled in the study that included 307 patients in the active group and 349 patients in the non-active group. The ratio of TBTB was significantly higher in the active group than that in the non-active group [hazard ratio (HR), 2.31; 95% CI, 1.70–3.14; p < 0.001]. With PSM, the proportion of tracheobronchial stenosis in the non-active group was significantly higher than that in the active group (HR, 1.84; 95% CI, 1.15–2.95; p = 0.011). Moreover, the number of patients with moderate to severe stenosis were significantly higher than that in the active group (HR, 4.13; 95% CI, 2.25–7.63; p < 0.001). Similar results were obtained with multivariate analysis. With 12 months of treatment, both therapeutic effective rate (84.7 vs. 68.2%; p = 0.009) and improvement rate of non-fibrotic tracheobronchial stenosis (79.1 vs. 47.4%; p = 0.022) were higher in the active group than that in the non-active group. Conclusion Active and regular bronchoscopy is conducive to early diagnosis of TBTB, combined with prompt anti-tuberculosis therapy, greatly reducing the occurrence of tracheobronchial stenosis and improving prognosis.